Sustainable Asset Management : Linking Assets People and Processes for Results - Lutchman, Roopchan (DEStech Publications, 2006)
Presents ways of maintaining and improving assets in utilities and manufacturing environments.
Keywords: Assets (Accounting); elektronické knihy; electronic books